2001
DOI: 10.1083/jcb.200103146
|View full text |Cite
|
Sign up to set email alerts
|

An effector region in Eps8 is responsible for the activation of the Rac-specific GEF activity of Sos-1 and for the proper localization of the Rac-based actin–polymerizing machine

Abstract: Genetic and biochemical evidence demonstrated that Eps8 is involved in the routing of signals from Ras to Rac. This is achieved through the formation of a tricomplex consisting of Eps8–E3b1–Sos-1, which is endowed with Rac guanine nucleotide exchange activity. The catalytic subunit of this complex is represented by Sos-1, a bifunctional molecule capable of catalyzing guanine nucleotide exchange on Ras and Rac. The mechanism by which Sos-1 activity is specifically directed toward Rac remains to be established. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
136
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 37 publications
8
136
0
3
Order By: Relevance
“…Remarkably, inhibition of N-WASP by wiskostatin in the testis in vivo did not lead to germ cell detachment or BTB damage, unlike Eps8, which is an actin-regulating protein with multiple functions, whose knockdown by RNAi would lead to germ cell loss and BTB damage in vivo (17). Although the Arp2/3 complex can serve as a downstream effector of Eps8 through the activation of Rac and WASP family verprolin-homologous protein (WAVE) (5,18), Eps8 has more diverse effects on the actin cytoskeleton that are not mediated through Arp2/3 complex, such as actin capping and bundling (19,20). Thus, the activation of Arp2/3 complex by N-WASP can be limited to actin cytoskeletal restructuring via actin branching, instead of maintaining junction integrity in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, inhibition of N-WASP by wiskostatin in the testis in vivo did not lead to germ cell detachment or BTB damage, unlike Eps8, which is an actin-regulating protein with multiple functions, whose knockdown by RNAi would lead to germ cell loss and BTB damage in vivo (17). Although the Arp2/3 complex can serve as a downstream effector of Eps8 through the activation of Rac and WASP family verprolin-homologous protein (WAVE) (5,18), Eps8 has more diverse effects on the actin cytoskeleton that are not mediated through Arp2/3 complex, such as actin capping and bundling (19,20). Thus, the activation of Arp2/3 complex by N-WASP can be limited to actin cytoskeletal restructuring via actin branching, instead of maintaining junction integrity in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the mechanism of stimulation of Sos exchange activity. The Sos DH domain is active for Rac1 exchange only when Sos is in a ternary complex with Eps8 and E3b1 (Scita et al, 1999(Scita et al, , 2001Innocenti et al, 2002). We investigated whether binding of interacting proteins to the SH3 domains can derepress the exchange activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case for the Vav GEF, intersectin 1L may need to be phosphorylated in order to derepress the DH domain (Crespo et al, 1997;Han et al, 1997;Schuebel et al, 1998;Aghazadeh et al, 2000). Similarly, binding of an additional protein in vivo may be necessary, as in the case of activation of Sos Rac1 exchange activity by formation of a ternary complex (Scita et al, 1999(Scita et al, , 2001Innocenti et al, 2002). Because our studies have utilized recombinant proteins that are missing the amino-terminal domains, a third possibility is that a missing amino-terminal component of intersectin 1L is involved in the regulation of exchange activity.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Several studies have shown that internalized EGFR are enzymatically active, are still phosphorylated and maintain association with many adaptor proteins. [43][44][45] In addition, it has been recently shown that interaction with some adaptor proteins, such as eps8, a protein involved in cytoskeletal reorganization and actin remodeling, 46 occurs only at endosomal level. 46 Furthermore, blocking of EGFR endocytosis by using a dynamin mutant results in downregulation of ERK and PI3K activation in response to EGF 47 and insulin.…”
Section: Egfr Internalization Is Altered In Pc3-ar Cellsmentioning
confidence: 99%
“…[43][44][45] In addition, it has been recently shown that interaction with some adaptor proteins, such as eps8, a protein involved in cytoskeletal reorganization and actin remodeling, 46 occurs only at endosomal level. 46 Furthermore, blocking of EGFR endocytosis by using a dynamin mutant results in downregulation of ERK and PI3K activation in response to EGF 47 and insulin. 48 Whether EGFR-AR interaction may be responsible for decreased EGFR signaling and internalization remains to be addressed; however, it is possible that such interaction disrupts the ability of the receptor to autophosphorylate by attenuating its intrinsic tyrosine kinase activity, determining as a consequence a reduction of internalization and PI3K activation.…”
Section: Egfr Internalization Is Altered In Pc3-ar Cellsmentioning
confidence: 99%